Delineating social livability through placemaking a case study for Subic Bay Freeport Zone's recreational nodes - Cabatit, Paulo E. (College of Architecture, University of the Philippines Diliman, 2026)
Social livability a people-centered urban design concept, aids in theses issues as it focuses on the city's culture and community. Together with placemaking, social livability could help define the city's qualities that provide inclusive vibrant places. Developments on the Philippines that can benefit from these types of urban revitalization methods are former military bases such as the Subic Bay Freeport Zone (SBFZ), SBFZ's existing infrastructure reflects boundaries which permeate in its urban morphologies, especially in its recreational nodes. From this perspective, studying former military bases requires a comprehensive approach that considers social livability and placemaking. Social livability indicators were gathered through literature review and spatial audits. Survey questionnaires and Public Space & Public Life survey (PSPL) gathered spatial and perception-based measures to evaluate its social livability. The data was evaluated through correlation and linear regression analysis to determine the weight of social livability indicators and how it was perceived by the respondents. This study offers insights into describing and visualizing social livability of the recreational nodes which showed potential in fostering social environments through residents' perception and pattern of activities. The results provide comprehensive assessment of the social livability of the recreational nodes within SBFZ, noting identity and image as its primary indicator. This study defines and visualizes the social livability within SBFZ's recreational nodes if the residents perceive it to foster community and social activities.